Sengketa Laut China Selatan yang Bersinggungan Dengan Zona Ekonomi Ekslusif Indonesia di Utara Kepulauan Natuna, Provinsi Kepulauan Riau (Mimbar Keadilan, 2023)
The purpose of this research is to describe China's unilateral claims in the South China Sea through the nine-dash line map that intersects with Indonesia's EEZ in accordance with UNCLOS 1982 where Indonesia finally took a stand on China's unilateral claims in the South China Sea in the northern sea of Natuna. It is hoped that this research can be useful as a basis for the development of science, especially in the field of international maritime law. This research uses a normative legal research method with statue approach and a case approach where various literature is related as secondary data that will strengthen the research arguments. Indonesia's relationship with China is heating up because China's unilateral claim in the waters of the South China Sea through a nine-dash line map is intersecting with the territory of Indonesia's maritime zone, the Exclusive Economic Zone of Indonesia in the Northern Natuna Islands of Riau Islands Province which has been recognized according to the United Nations Convention on the Law of the Sea (UNCLOS) 1982. The results showed that the nine-dash line claims by China did not comply with UNCLOS 1982, a misunderstanding between Indonesia and China led the two countries to mediate and requested that China respect the provisions of international law, especially UNCLOS 1982 as the world maritime constitution.